Waqf : aporverty alleviation tool in Malaysia / Che' Khalilah Mahmood, Nor Haliza Hamzah and Wan Nor Hafidzah Wan Mohd - Mahmood, Che' Khalilah; Hamzah, Nor Haliza; Wan Mohd, Wan Nor Hafidzah (Penerbit Universiti Teknologi MARA Cawangan Pahang, 2017)
Waqf is a charitable instrument in Islam that has many roles including helping the have-nots in the society. This paper discusses Waqf as a poverty alleviation tool in Malaysia, the key roles of Waqf institutions and the issues faced by those institutions in Malaysia. Â This is a conceptual paper which has been developed through literature reviews some of the current literature, journals, report and news on the subject matter. The findings includes the d iscussion on Waqf as a poverty alleviation tool which include socio-economic development for the poor and supporting in providing the facilities such as mosque, hospitals, orphanage shelters and others.